Effect of C242T Polymorphism in the Gene Encoding the NAD(P)H Oxidase p22(phox) Subunit and Aerobic Fitness Levels on Redox State Biomarkers and DNA Damage Responses to Exhaustive Exercise: A Randomized Trial - Cho, Su-Youn (Int J Environ Res Public Health, 2020)
NAD(P)H oxidases (NOXs) constitute a principal source of cellular reactive oxygen species (ROS) and contribute to exercise-induced ROS production in the skeletal muscle. Here, we aimed to investigate the effect of single-bout exhaustive exercise on redox state biomarkers and oxidative DNA damage based on the C242T polymorphism in the gene encoding NOXs subunit p22(phox) (CYBA) and aerobic fitness levels. We enrolled 220 healthy adults in their 20s (men, n = 110; women, n = 110), who were divided into CC genotype and T allele groups through the analysis of the CYBA C242T polymorphism. Furthermore, maximum oxygen uptake (VO(2)max) was evaluated to divide subjects into high fitness (HF; 70th percentile for aerobic fitness) and mid-range fitness (MF; 40–60th percentile for aerobic fitness) groups, with a total of 32 subjects assigned to four groups (eight subjects per group): CC genotype and HF group (CC + HF), CC genotype and MF group (CC + MF), T allele and HF group (T + HF), and T allele and MF group (T + MF). All subjects performed treadmill running exercise at 85% of VO(2)max until exhaustion. Plasma lactate, malondialdehyde (MDA), superoxide dismutase (SOD), and lymphocyte DNA damage (tail DNA percentage [TD], tail length [TL], and the tail moment [TM]) were measured in the blood samples obtained immediately before (IBE), immediately after (IAE), and 30 min after exercise (30 MAE). Plasma lactate levels, SOD activities, and lymphocyte DNA damage markers (TD, TL, and TM) were significantly increased at IAE than that at IBE and significantly decreased at 30 MAE (p < 0.05). All groups displayed increased plasma MDA levels at IAE rather than at IBE, with CC + MF being significantly higher than T + HF (p < 0.05); only the CC + HF and T + HF groups exhibited a significant reduction at 30 MAE (p < 0.05). Moreover, TL at IAE was significantly higher in the CC + MF group than in the T + HF group (p < 0.05), and significantly higher in the CC + MF and CC + HF groups than in the T + HF group at 30 MAE (p < 0.05). TM was significantly higher in the T + MF than in the T + HF group at IAE (p < 0.05) and that of CC + MF was significantly higher than CC + HF and T + HF values at IAE and 30 MAE (p < 0.05). These results suggest that single-bout exhaustive exercise could induce peripheral fatigue and the accumulation of temporary redox imbalance and oxidative DNA damage. Moreover, high aerobic fitness levels combined with the T allele may protect against exercise-induced redox imbalance and DNA damage.